Partisipasi Anggota Terhadap Kelompok Tani Tumangkokow Di Desa Kopiwangker Kecamatan Langowan Barat Kabupaten Minahasa - Waladow, Teofilus Miliano; Pangemanan, Paulus Adrian; Dumais, Joachim Noch Karel (Sam Ratulangi University, 2023)
This study aims to determine the level of member participation in the Tumangkokow Farmer Group in Kopiwangker Village. The research was conducted in Kopiwangker Village, West Langowan District, Minahasa Regency. The data collection method is a survey method. Interview data collection techniques using questionnaires. The results of this study using the Likert Scale measurement indicate that the participation of members of the Tumangkokow Farmer Group in Kopiwangker Village, Langowan Barat District, Minahasa Regency using the Likert Scale measurement is classified as active, measured from the planning, implementation, monitoring and evaluation of farming activities with a value of 77.02%. Members have participated in farmer groups with indicators of attending meetings, making decisions, stages of planting and stitching, fertilizing, pest and disease control and harvesting and post-harvesting are in the very active category and participation of members in giving opinions, stages of tillage, cleaning, monitoring and measuring the production of farming activities is in the active category.